(untitled) (Research, Society and Development, 2021)
Objective: To report the experiences of undergraduate nursing students experienced during the collection of project data that sought to know the situations of violence in the daily lives of people with disabilities who live in the rural context. Methodology: Descriptive study of the experience report type, developed from a qualitative research carried out through semi-structured interviews with people with disabilities or their main caregivers, in the case of minors under 18 years old or people with intellectual disabilities. The data collection of the project that supported this report took place from July 2018 to August 2019. Results: The experience allowed us to unveil the challenges experienced by people with disabilities who live in rural settings and their families with regard to financial difficulties, geographical distance and access to services. It also allowed the identification of different forms of violence experienced by people with disabilities, such as physical, sexual, psychological violence and social exclusion. Conclusion: The experience of developing a study with people with disabilities in the rural context made it possible to understand the magnitude of the phenomenon of violence and allowed the perception of the relevance of studying its impacts with different populations and scenarios. Still, it brought to the fore the urgency of a different look regarding people with disabilities who live in this unique context in order to provide comprehensive health care to this population.